Engineering Infrequent DNA Nicking Endonuclease by Fusion of a BamHI Cleavage-Deficient Mutant and a DNA Nicking Domain - Xu, Shuang-yong (Frontiers in Microbiology, 2022)
Strand-specific DNA nicking endonucleases (NEases) typically nick 3-7 bp sites. Our goal is to engineer infrequent NEase with >8 bp recognition sequence. A BamHI catalytic-deficient mutant D94N/E113K was constructed, purified and shown to bind and protect GGATCC site from BamHI restriction. The mutant was fused to a 76-amino acid (aa) DNA nicking domain of phage Gamma HNH (gHNH) NEase. The chimeric enzyme was purified and it was shown to nick downstream of a composite site 5’ GGATCC-N(4-6)-AC CGR 3’ (R, A or G) or to nick both sides of BamHI site at the composite site 5’ CCG GT-N5-GGATCC-N5-AC CGG 3’ (the down arrow indicates the strand shown is nicked; the up arrow indicates the bottom strand is nicked). Due to the attenuated activity of the small nicking domain, the fusion nickase is active in the presence of Mn2+ or Ni2+ and it has low activity in Mg2+ buffer. This work provided a proof of concept that chimeric NEases could be engineered utilizing the wide range of binding specificities of Type II restriction endonucleases (REases) in fusion with a nicking domain to generate infrequent NEases, that bridges the gap between natural REases and homing endonucleases. The engineered chimeric NEase provided a framework for further optimization in molecular diagnostic applications.